STUDYING DOSE-DEPENDENT ENDOTHELIO- AND CARDIOPROTECTIVE ACTIVITY OF SELECTIVE ARGINASE II INHIBITOR IN HYPERHOMOCYSTEINE-INDUCED ENDOTHELIAL DYSFUNCTION - Vladimir Yakushev; Nikolaj Filippenko; Irina Kizilova; Mikhail Korokin; Evgeniya Beskhmelnitsyna; Anna Litvinova (Belgorod National Research University, 2016)
This paper deals with the study of endothelio- and cardioprotective activity of arginase II selective inhibitor, the substance under the code ZB49-0010C in the model of hyperhomocysteine-induced endothelial dysfunction. The results of the studies prove the presence in the arginase II selective inhibitor, the substance under the code ZB49-0010C, dosedependent endothelioprotective and cardioprotective activity, which expression increases with the increase in dose and is maximum at a dose of 10 mg/kg. The research was partially supported by the grant of the President of the Russian Federation №MD-4711.2015.7.